Subcutaneously administered methotrexate for rheumatoid arthritis, by prefilled syringes versus prefilled pens: patient preference and comparison of the self-injection experience - Demary, Winfried (Dove Medical Press, 2014)
PURPOSE: This multicenter, randomized, crossover study compared preference, ease of use, acceptability, satisfaction, and safety of repeated subcutaneous (SC) self-administrations with prefilled pens and prefilled syringes delivering methotrexate (MTX), in patients with rheumatoid arthritis (RA). PATIENTS AND METHODS: The study (ClinicalTrials.gov number NCT01793259) enrolled 120 patients requiring initiation or intensification of MTX therapy for RA. Patients were randomized to receive the test drug, a prefilled pen (Metex(®) PEN/Metoject(®) PEN), or the reference drug, a prefilled syringe (Metex(®)/Metoject(®)), at doses of 15, 17.5, or 20 mg MTX SC once a week for 3 weeks. This was followed by receipt of the reference drug (prefilled syringe) or the test drug (prefilled pen) in a crossover design, with each patient serving as his/her own control. Questionnaires regarding patient preference, the Self-Injection Assessment Questionnaire (SIAQ), and diaries regarding local tolerability were used to document outcomes. RESULTS: Overall patient preference for the MTX prefilled pen was 75% (P<0.0001). In a six-item questionnaire, 73% to 76% of the patients preferred the prefilled pen in relation to use, acceptability, and satisfaction, and 67% of the patients confirmed that it did not take much effort to overcome SC self-injection with the pen. The SIAQ showed no clinical differences, in any domain scores, between both devices. Overall patient attitude towards self-injection at baseline was positive, as was patient experience with both devices during the study. As well, 92% of physicians and study nurses indicated that they would recommend the MTX prefilled pen to patients for future MTX treatment. The formulations were generally well tolerated. CONCLUSION: SC self-injection of MTX with a prefilled pen was generally preferred, by patients with RA, over a prefilled syringe with regard to use, acceptability, and satisfaction. This is supported by the strong appreciation of their attending study nurses and physicians, for its convenience.